2012
DOI: 10.5089/9781475505368.001
|View full text |Cite
|
Sign up to set email alerts
|

Riding Global Financial Waves: The Economic Impact of Global Financial Shocks on Emerging Market Economies

Abstract: Over the past two decades, most emerging market economies witnessed two key developments. A marked process of financial integration with the rest of the world, arguably turning these economies more vulnerable to global financial shocks; and an improvement of macroeconomic fundamentals, helping to increase their resiliency to these shocks. Against a backdrop of these opposing forces, are these economies more vulnerable to global financial shocks today than in the past? Have better fundamentals offset increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The results for all the countries point to the fact that the probability of staying in a recession is less than that of staying in an expansion or boom. Owing to the number of distinctive characteristics of the BRICS economies, Kutu and Ngalawa (2016) reveal that the "BRICS countries are moving towards an inflation targeting/floating exchange rate system (similar monetary policy regime shifts); the adoption of countercyclical monetary and fiscal policies as against the previous procyclical or acyclical policies; are prone to the same external shocks due to the dominant influence of the US Dollar on their economies (Adler, Tovar Mora, 2012) and are EMEs with a per capita income lower than the average per capita income in the G7 countries (Calderón, Yeyati, 2009)". These distinctive characteristics are also consistent with the findings of this study, hence, may have informed their establishment of the BRICS' Development Bank as an alternative source of funds to the IMF and World Bank in their expedition to develop the bloc.…”
Section: Resultsmentioning
confidence: 99%
“…The results for all the countries point to the fact that the probability of staying in a recession is less than that of staying in an expansion or boom. Owing to the number of distinctive characteristics of the BRICS economies, Kutu and Ngalawa (2016) reveal that the "BRICS countries are moving towards an inflation targeting/floating exchange rate system (similar monetary policy regime shifts); the adoption of countercyclical monetary and fiscal policies as against the previous procyclical or acyclical policies; are prone to the same external shocks due to the dominant influence of the US Dollar on their economies (Adler, Tovar Mora, 2012) and are EMEs with a per capita income lower than the average per capita income in the G7 countries (Calderón, Yeyati, 2009)". These distinctive characteristics are also consistent with the findings of this study, hence, may have informed their establishment of the BRICS' Development Bank as an alternative source of funds to the IMF and World Bank in their expedition to develop the bloc.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for applying rigid exchange rate is that countries in transition show signs of "fear to float" (Edwards, 2006). On the other hand, the empirical evidence that provides argument that exchange rate reacts adversely to real shock by stabilizing the economy, makes a strong case for more accommodative exchange rate as a shock absorber (Blanchard, 2010;Adler and Tovar, 2012). Based on the empirical evidence for transition countries, particularly in the Western Balkan region, exchange rate has often played a fundamental role in macroeconomic stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…The same result was found by Blanchard (2010) who claims that the fixed exchange rate has a limited effect on output, and growth declined during the crisis. Adler and Tovar (2012) in another recent study showed that exchange rate flexibility can mitigate the impact of the adverse effect of financial shocks, particularly to the emerging economies that are greatly financially integrated.…”
Section: Introductionmentioning
confidence: 99%
“…20 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 Brazil's debt, commodities, and derivatives markets are more advanced; Brazilian banks operate in a more competitive and generally better regulated market; and, as noted above, Brazil's capital controls regime has been more flexible. One recent study suggests that greater integration with global financial markets reduces economic volatility -but only when countries have flexible exchange rates, which Brazil has had since 1999, while India has tentatively floated the rupee only since 2007 (Adler and Tovar 2012). Overall, Brazilian policymakers can be more confident of their economic position vis-à-vis global markets -which likely gives them confidence to speak out.…”
Section: Accounting For Similarity and Divergence In Fsmentioning
confidence: 93%